Correlation between value of Hba1c and degree of sensorineural hearing loss in type 2 diabetics - Kumar, Prateek; Mishra, Sarita Kumari; Prakash, Ved; Singh, Rakesh Kumar (International Journal of Research in Medical Sciences, 2023)
Background: Diabetes mellitus and hearing loss are common public health problems. Sensorineural hearing loss in Type 2 diabetes mellitus patients is an underestimated complication. The aim was to study the correlation between level of HbA1c and degree of sensorineural hearing loss. Methods: It was a cross sectional study carried on 130 known cases of T2DM, aged 25-50 years. Various confounding factors such as coexisting hypertension, ear disease, ototoxic drug intake, any neuropathic disorder was excluded in advance. All patients underwent clinical ear examination and pure tone audiometry test. Their level of HbA1c was measured. This value of HbA1c was correlated with the hearing threshold. Results: Out of 130, 58 subjects had normal hearing while 72 had hearing impairment. Among subjects (72 out of 130) having hearing impairment, significant correlation (p-value 0.035 for right ear and 0.029 for left ear) between hearing threshold and HbA1c was found. Also, level of HbA1c significantly (p-value 0.049) correlated with degree of hearing loss. Conclusions: Hearing loss is an underestimated complication of T2DM. This needs to be addressed with periodic hearing assessment of diabetes patients.